Video Gaming in Croatia: Empirical Research - Ljubica MILANOVIĆ GLAVAN; Karlo LEMAC (Communications of International Proceedings, 2022)
In the recent decade the video game industry has grown to be the biggest area of popular entertainment, which, starting from releasing very simple games with bad graphics, quickly evolved into interactive animations which one could call art. Considering the visual excitement one can get from playing a videogame, the level of satisfaction can be matched to watching a movie. So, today, without a doubt, video industry has become a leading industry among all the other media industries, affecting both the young and the old population. This paper explains the state of video gaming industry, both in the world and, in more detail, in the territory of Croatia. Furthermore, research was conducted on the population of gamers in Croatia, with the aim of examining their consumption, habits and attitudes about video games. In order to show the situation of Croatian consumers in the video game market, the survey collected primary data from the population of the Republic of Croatia. That data was analysed and then compared with the collected, secondary data related to world consumption.
Keywords: video gaming industry; video games; empirical research; Croatia.